REFORMULASI HUKUM DAN PERBAIKAN ETIKA TERHADAP KEPOLISIAN ATAS PELANGGARAN PENGGUNAAN GAS AIR MATA STADION KANJURUHAN - Akbar, Sahda Saraswati; Safitri, Nadila; Yulistio, Muhammad Raihan; Fath, Al; Maula, Putri Ni’matul (Jurnal Hukum Statuta, 2022)
The police as a state tool that functions to maintain security, maintain order, protect and serve the community should be able to provide protection to the community. However, what is happening now is quite the opposite. As happened at the Kanjuruhan stadium where the police in controlling the crowd actually committed human rights violations. Human rights violations committed by the police show that at this time the police have not been able to position themselves proportionally. The purpose of this study was to determine the legitimacy of the use of tear gas in controlling the crowd at the Kanjuruhan Stadium by the police and to find out the legal reformulation and ethical improvement of the violation of mass control at the Kanjuruhan Stadium by the police. This study uses a normative juridical research method with a statute approach and a conceptual approach regarding the rules that should be the basis for mass control carried out by the police. Based on the results of the study, in terms of the validity of the actions taken by the police, it was stated that they did not take into account the level of threat or the safety of the community. Therefore, the way that can be done by the police in order to build a civilian character and improve their image is to carry out legal reformulation and ethical improvement over the violation of the Kanjuruhan Stadium crowd control by the police. The recommendations that the author gives to the PSSI institution, the match organizers, the police, the general public to the government so that this paradox does not happen again.